2010
DOI: 10.1007/s11655-010-0563-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the medical expenditure of Chinese medicine and integrative medicine treatment for influenza a (H1N1) in the fever clinics

Abstract: The H1N1 patients in the fever clinic who received Chinese medicine treatment had a higher clinical recovery proportion than those who received integrated Chinese and Western medicine treatment with lower medical cost. However, due to small sample size of the Chinese medicine group in the study, the conclusion needs further confirmation by studies with large sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…TCM therapy was also recommended as a second-line treatment for H7N9 infection. Previous studies have demonstrated that TCMs may have beneficial effects on patients with avian influenza [11,12]. Our univariate logistic regression analysis indicated that the duration of TCM therapy could be partially associated with the prognosis in H7N9-infected patients.…”
Section: Discussionmentioning
confidence: 54%
“…TCM therapy was also recommended as a second-line treatment for H7N9 infection. Previous studies have demonstrated that TCMs may have beneficial effects on patients with avian influenza [11,12]. Our univariate logistic regression analysis indicated that the duration of TCM therapy could be partially associated with the prognosis in H7N9-infected patients.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, while some cellular consequences of TREM-1 activation such as upregulation of chemokines, cytokines, matrix metalloproteases, and post transcriptional gene silencing (PTGS)/COX2 are similar to those observed upon lipopolysaccharide stimulation, which is consistent with a core inflammatory response, other immunomodulatory factors, including secreted phosphoprotein 1 (SPP1) and M-CSF, are induced selectively in response to TREM-1 cross-linking [38]. In line with these findings, inhibition of TREM-1 in vivo was shown to reduce release of MCP-1, TNFα, IL-1β, IL-6, and M-CSF [28,36,4044]. Blockade of TREM-1 is a promising approach in a variety of inflammation-associated disorders including sepsis, cancer, rheumatoid arthritis and other serious diseases with unmet clinical needs [28,36,3941,4346].…”
Section: Introductionmentioning
confidence: 74%
“…All the studies were conducted in the general population. Research was conducted on hand hygiene [107], [108], infection control [109], facemask use [108], [110], school closure [111], [112], physical exercise [113], alternative therapies including tea catechin [114], passive immunotherapy for management of severe cases of influenza infection [115] and use of traditional medicine [116]. One modelling study assessed methods to improve the effectiveness of different antiviral strategies [117], and another evaluated combinations of methods including enhanced surveillance with isolation, segregation and personal protective equipment to limit influenza transmission in closed environments [118].…”
Section: Resultsmentioning
confidence: 99%